INTERPERSONAL APPRAISAL COMMUNICATION STRATEGY IN IMPROVING SERVICE QUALITY (Case Study BRI Regional Jakarta 1) - Kristyawan Kristyawan; Afdal Makkuraga Putra (MediaKom : Jurnal Ilmiah Komunikasi, 2023)
The development and growth of housing loans (KPR), especially at BRI, is very fast, so qualified collateral appraisal is needed. Much research has been done on interpersonal communication strategies. The implementation of an interpersonal communication strategy that is not yet optimal and the quality of the appraisal staff that has not been achieved at the BRI Regional Office Jakarta 1 Consumer Loan Factory (CLF) form the basis of this research. As the main theoretical foundation of this research, social exchange theory and DeVito's interpersonal communication theory are used to provide more operational dimensions in viewing the structure of social exchange. The research objective to be achieved is to determine interpersonal appraisal communication strategies in improving service quality. In this study, researchers used a qualitative method (Case Study). Researchers use the constructivist paradigm as a structure of thought. The results in this study show that communication carried out by an BRI appraisal takes place in two directions and vice versa. Communication carried out by an appraisal has an influence on improving the quality of services performed. Appraisal is an official who is responsible for evaluating credit collateral and monitoring other matters related to collateral. The strategies undertaken include prudent, maneuverable, accurate. Communication carried out by an appraisal has an influence on improving the quality of services performed. Appraisal is an official who is responsible for evaluating credit collateral and monitoring other matters related to collateral. The strategies undertaken include prudent, maneuverable, accurate. Communication carried out by an appraisal has an influence on improving the quality of services performed. Appraisal is an official who is responsible for evaluating credit collateral and monitoring other matters related to collateral. The strategies undertaken include prudent, maneuverable, accurate.